A Class of Utility Functions Containing all the Common Utility Functions - Brockett, Patrick L.; Golden, Linda L. (Management Science, 1987)
This paper presents a class of utility functions (class A ∞ ) that contains all of the utility functions commonly used for mathematical modeling: the class consisting of those utility functions whose derivatives alternate in sign. A simple representation via mixtures of exponential utilities is provided for this class which is both mathematically convenient and conducive to functional operations. A connection with Laplace transforms and the resultant implications for preference relations, aggregation and utility assessment are discussed.